Research on Automation and Efficiency Optimization in Intelligent Logistics Centers — Taking JD Logistics’ “Asia No.1” as an Example - Chijing Deng (Journal of World Economy, 2025)
This study investigates how automation technology in intelligent logistics centers can significantly enhance logistics efficiency, taking JD Logistics’ “Asia No.1” smart logistics center as a case example. By analyzing the implementation methods of highly automated operations and their impact on operational efficiency, the research finds that large-scale application of artificial intelligence, big data, cloud computing, and robotics can build a comprehensive intelligent logistics system. This system achieves full-process intelligence and unmanned operations in logistics, greatly improving operational efficiency. In addition, the study explores the application effects of automation technology in different logistics links and provides insights for the design and management of future logistics centers.